PERAN GURU PENDIDIKAN DALAM MEMBENTUK KARAKTER SISWA-SISWA DI SMK DARUT TAQWA - Moch Ridlwan Al-Khoir (Almustofa Journal of Islamic Studies and Research, 2025)
This research is motivated by concerns over the declining character of students due to the negative influences of modern times, such as social media, technology, and complex social environments. These challenges highlight the urgent need to strengthen character education in schools, especially through the role of teachers. The main objective of this study is to explore the role of teachers in instilling character values in students and to identify the supporting and inhibiting factors in the character-building process at SMK Darut Taqwa. This study employs a descriptive qualitative approach, using data collection techniques such as field observation, structured interviews, and documentation. The findings reveal that teachers play a central role as educators, mentors, role models, and motivators in shaping students' character. The core values emphasized include honesty, responsibility, discipline, and independence. The conclusion underscores the importance of synergy between teachers, schools, parents, and the surrounding environment in building students who are morally upright and independent—capable of facing the challenges of the modern era with integrity and strong personal values.